2012
DOI: 10.1016/j.ccr.2011.12.021
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model of MYC-Driven Medulloblastoma

Abstract: SUMMARY Medulloblastoma (MB) is the most common malignant brain tumor in children. Patients whose tumors exhibit overexpression or amplification of the MYC oncogene (c-MYC) usually have an extremely poor prognosis, but there are no animal models of this subtype of the disease. Here we show that cerebellar stem cells expressing Myc and mutant Trp53 (p53) generate aggressive tumors following orthotopic transplantation. These tumors consist of large, pleiomorphic cells and resemble human MYC-driven MB at a molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
310
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(329 citation statements)
references
References 57 publications
14
310
2
3
Order By: Relevance
“…The resultant tumors showed that the LCA phenotypes were highly aggressive, and transcriptionally resembled group 3 MB. MYC withdrawal caused complete tumor regression (Pei et al 2012). These data suggest that MYC is a significant contributor to the initiation, maintenance, and progression of this disease (see Gabay et al 2013).…”
Section: Myc In the Group 3 Subgroupmentioning
confidence: 88%
See 2 more Smart Citations
“…The resultant tumors showed that the LCA phenotypes were highly aggressive, and transcriptionally resembled group 3 MB. MYC withdrawal caused complete tumor regression (Pei et al 2012). These data suggest that MYC is a significant contributor to the initiation, maintenance, and progression of this disease (see Gabay et al 2013).…”
Section: Myc In the Group 3 Subgroupmentioning
confidence: 88%
“…However, because deprivation of MYC and MYCN in group 3 and group 4 models either induce senescence or apoptotic cell death (Swartling et al 2010;Pei et al 2012), several strategies are being considered to suppress MYC function either by regulating its expression or preventing its binding to partner proteins.…”
Section: Therapeutic Strategies For Medulloblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…La mayoría muestra la histología clásica, aunque también en menor medida la variante de células grandes/anaplásica 16 . Los meduloblastomas de este grupo parecen originarse de los precursores neuronales de la capa granular externa de la región subventricular 22 .…”
Section: Subgrupos Molecularesunclassified
“…Les auteurs en concluent que les MB WNT sont issus de la transformation de progéniteurs neuronaux de la lèvre rhombique inférieure, dans lesquels s'opère une synergie entre mutations de CTNNB1 et TP53 qui induit l'oncogenèse. L'expression de la Cre recombinase dans ce modèle n'étant pas restreinte à la lèvre rhombique, cette hypothèse est encore controversée [8]. …”
unclassified